Modeling the impacts of climate change on mass balance and discharge of Eklutna Glacier, Alaska, 1985–2019. Issue 265 (5th October 2021) - Geck, Jason; Hock, Regine; Loso, Michael G.; Ostman, Johnse; Dial, Roman
Abstract: Alaska's largest city, Anchorage, depends on Eklutna Glacier meltwater for drinking water and hydropower generation; however, the 29 km 2 glacier is rapidly retreating. We used a temperature-index model forced with local weather station data to reconstruct the glacier's mass balance for the period 1985–2019 and quantify the impacts of glacier change on discharge. Model calibration involved a novel combination of in situ, geodetic mass-balance measurements and observed snowlines from satellite imagery. A resulting ensemble of 250 best-fitting model parameters was used to model mass balance and discharge. Eklutna Glacier experienced a significant negative trend (−0.31 m w.e. decade −1 ) in annual mean surface mass balance (mean: −0.62 ± 0.06 m w.e.). The day of the year when 95% of annual melt occurs was five days later in 2011–19 than in 1985–93, demonstrating a prolongation of melt season (May–September). Modeled mean specific discharge increased at 0.14 m decade −1, indicating peak water, the year when annual discharge reaches a maximum due to glacier retreat, has not been reached. Four of the five highest discharge years occurred since 2000. Increases in discharge quantity and melt season length require water resource managers consider future decreased discharge as the glacier continues to shrink.